Pampa prey exhibition: instrument for dissemination and scientific literacy - Moura, Ubiraci Silva de; Cadematori, Cristina Vargas (Revista Hipótese, 2021)
The present work highlights the importance of biological exhibitions in the dissemination and scientific literacy, especially when associated with digital tools that enable greater interaction with the public. The positive impressions, described by the visitors, about the exhibition “Birds of prey of the Pampa”, demonstrated the interest of the public, which manifested itself in several aspects, from more technical to aesthetic and cultural. The success of the exhibitions is linked to the balance between graphic and didactic elements, ensuring greater visibility and providing additional information to the public, triggering a cooperative feeling between the exhibition and the visitors.
Keywords: Vertebrates; Environmental education; Taxidermy